Adverse events in different administration routes of amiodarone: a pharmacovigilance study based on the FDA adverse event reporting system - Yang, Jingrong; You, Mengfan; Wang, Jingxin; Sun, Rongfei; Han, Lili; Liu, Xiaonan; Niu, Kaibin; Xing, Kaidi; Sun, Juanping; Su, Wenge; Wang, Yifei (Frontiers in Pharmacology, 2025)
BackgroundArrhythmias are prevalent cardiac disorders with significant impacts on patient quality of life and mortality. Amiodarone, a class III antiarrhythmic agent, is widely used to manage both atrial and ventricular arrhythmias due to its efficacy in prolonging the cardiac action potential and its multiple antiarrhythmic properties. While clinical trials have highlighted the safety and efficacy of amiodarone, there is limited real-world data on adverse events (AEs) associated with different administration routes. This study aims to address this gap by utilizing the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) to investigate the spectrum and timing of AEs related to amiodarone administration through disproportionality analysis and stratification methods.MethodsData from the FAERS database were analyzed using disproportionality analysis and reporting odds ratio (ROR) methods for comparative analysis, and the Weibull distribution for time-to-adverse-event analysis. The study examined data from 2004 through the first quarter of 2024 to analyze adverse event signals and the time of occurrence between intravenous and oral amiodarone administration.ResultsA total of 16,749 records of adverse reactions associated with amiodarone were identified. Among these, 2,412 events were related to intravenous amiodarone, and 8,220 events were related to oral amiodarone. The analysis revealed that cardiac and hepatic AEs were more common with intravenous administration, while pulmonary and thyroid-related AEs were more frequent with oral administration. Furthermore, the onset of adverse reactions varied significantly between the routes. The Weibull distribution analysis showed a median onset time of 5 days for intravenous administration compared to 74 days for oral administration. Both routes exhibited early failure-type signals, indicating a decreasing risk of AEs over time.ConclusionAmiodarone exhibits varying adverse drug reactions and onset times across different routes of administration. Clinicians should carefully consider these differences when selecting the administration route to balance the risks of adverse reactions with therapeutic benefits.